(untitled) (CIPEEX, 2022)
PSYCHIATRIC DISORDERS ARE ALTERATIONS IN THE FUNCTIONING OF THE MIND THAT REFLECT ON THE PERFORMANCE AND QUALITY OF LIFE OF INDIVIDUALS. IN THE CASE OF WOMEN, ADDING THESE DISTURBANCES TO THE GESTATIONAL MOMENT, THESE DISORDERS CAN WORSEN, DUE TO THE INTENSE PHYSICAL AND PSYCHOLOGICAL CHANGES THAT OCCUR DURING THIS PERIOD. THUS, AS A RESULT OF THE GROWING USE OF PSYCHOTROPIC DRUGS AND THEIR IMPACTS, THE PRESENT RESEARCH PRESENTED THE FOLLOWING GUIDING QUESTION: €ŒWHAT ARE THE REPERCUSSIONS THAT THE USE OF PSYCHOTROPIC DRUGS CAN GENERATE DURING PREGNANCY, IN THE NEWBORN AND IN EARLY CHILDHOOD".